2020
DOI: 10.1088/2633-1357/aba739
|View full text |Cite
|
Sign up to set email alerts
|

Identifying regional COVID-19 presence early with time series analysis

Abstract: The first confirmed case of COVID-19 in the United States was January 20, 2020 in Washington, while the first globally confirmed cases were in China in December 2019. The CDC's Influenza-like Illness Surveillance Network is used to track the amount of people who seek medical attention for influenza-like illnesses, along with the illness cause. The metric rILI- is used to assess the amount of people who test negative for influenza or any other specific cause. To assess the evidence of COVID-19 presence in the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It is proposed to study the dynamic of COVID-19 in every country as a polynomial model that can be correlated each other according to optimize prediction answers, there is no mathematical model that adapts to the predictions such as the number of infected people and the quantity of deceased people (Kruse & Alkhushayni, 2020;Kucharski et al, 2020;Marmarelis, 2020;Ping, 2020;Rustam et al, 2020;Trigger & Czerniawski, 2020;Wang et al, 2020;Yuankang et al, 2020). Hence, every adaptive coefficients of matrix can be translated as interchanging information between every country, regarding to share many details and steps that could deal with this pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…It is proposed to study the dynamic of COVID-19 in every country as a polynomial model that can be correlated each other according to optimize prediction answers, there is no mathematical model that adapts to the predictions such as the number of infected people and the quantity of deceased people (Kruse & Alkhushayni, 2020;Kucharski et al, 2020;Marmarelis, 2020;Ping, 2020;Rustam et al, 2020;Trigger & Czerniawski, 2020;Wang et al, 2020;Yuankang et al, 2020). Hence, every adaptive coefficients of matrix can be translated as interchanging information between every country, regarding to share many details and steps that could deal with this pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in the rate of ED encounters for CLS occurred during both March-September 2020, a known period of the initial COVID-19 surge, and October 2019-February 2020, before there was any known spread of COVID-19. While previous studies reported an early presence of COVID-19 due to increases in ILI or non-influenza ILI during early 2019-2020 [13][14][15][16][17][18], our findings offer a more detailed perspective as we examined visits for symptoms consistent with COVID-19 and separately for influenza and non-influenza-ILI. Since all three symptom categories were not mutually exclusive, it can be difficult to evaluate whether the increases observed in other studies with combined categories were indeed due to increases in CLS.…”
Section: Discussionmentioning
confidence: 97%
“…Evidence suggests that COVID-19 might have been present in China [1,2], Europe [3][4][5][6][7][8] and in the United States (US) [9][10][11] much earlier than 20 January 2020 when the first COVID-19 case [9], or January 30 when the first person-to-person transmission were reported in the US [12]. In the US, the early spread of COVID-19 was suggested by increases in Influenza-Like Illness (ILI) reported by the ILI Surveillance Network (ILINet), the Centers for Disease Control and Prevention (CDC) database [13][14][15][16]. An online survey in the US showed an increase in ILI among influenza-vaccinated adults in 2019-2020 compared to the previous year [17], and a study using electronic health records reported a significant increase in ED visits for cough and excess hospitalizations for acute respiratory failure between late December 2019 and February 2020 [18].…”
Section: Introductionmentioning
confidence: 99%